2023
DOI: 10.1186/s12913-023-09401-y
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare services gap analysis: a supply capture and demand forecast modelling, Dubai 2018–2030

Nahed Monsef,
Eldaw Suliman,
Elham Ashkar
et al.

Abstract: Background Health systems aim to provide a range of services to meet the growing demand of Dubai's heathcare system aims to provide a range of services to meet the growing demand of its population health needs and to ensure that standards of easy access, quality, equity and responsiveness are maintained. Dubai Health Authority (DHA) uses health services planning tools to assess the health needs of its population and sets priorities and effective regulatory strategies to achieve equilibrium of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Globally, countries such as the United States, Australia, the United Kingdom, Canada, and China are at the forefront of research activities in this field. This may reflect these nations’ advantages in medical research infrastructure and funding, as well as their emphasis on improving public health quality ( 18 ). Regarding author influence, scholars such as Ferreira P. H., Maher C. G., and Hartvigsen J. have played pivotal roles in advancing the field.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, countries such as the United States, Australia, the United Kingdom, Canada, and China are at the forefront of research activities in this field. This may reflect these nations’ advantages in medical research infrastructure and funding, as well as their emphasis on improving public health quality ( 18 ). Regarding author influence, scholars such as Ferreira P. H., Maher C. G., and Hartvigsen J. have played pivotal roles in advancing the field.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to suggest a disconnect between customer needs (demand) and provider offerings (supply). As seen in studies in Italy , 34 and United Arab Emirates, 35 such disparities lead to inefficiencies and poor performance of health services and systems. Moreover, unlike the UK’s National Health Service, most developing health systems, including Nigeria, lack policy guidelines for the commissioning and on-going evaluation of POCTs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study in Brazil showed that it is important to address the population's health needs and problems, indicating that in this country, the priority areas are not as obvious as in the GCC [9]. Thus, improving healthcare quality is a national priority for GCC governments in fulfilling the present and future health needs of the population [10]. This role can, however, only be accomplished by focusing on the quality areas in research, since quality has emerged as one of the most important factors influencing patients' choices between government and private hospitals in the GCC countries.…”
Section: Introductionmentioning
confidence: 99%